ANANALISIS PENGARUH RELIGIUSITAS DAN ETIKA BISNIS ISLAM TERHADAP MINAT BELI ONLINE PRODUK MAKANAN HALAL MAHASISWA PRODI EKONOMI SYARIAH PADA PERGURUAN TINGGI KEAGAMAAN ISLAM (PTKI) DI KABUPATEN BONDOWOSO - Wardaniyah; Eko Raharto (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2026)
This study aims to test and empirically prove (1) the influence of religiosity on the interest in buying halal food products online for students of Islamic economics study programs at Islamic religious colleges (PTKI) in Bondowoso Regency. (2) the influence of Islamic business ethics on the interest in buying halal food products online for students of Islamic economics study programs at Islamic religious colleges (PTKI) in Bondowoso Regency. This type of research uses a quantitative approach. The population of this study was students of Islamic economics study programs at Islamic religious colleges (PTKI) in Bondowoso Regency, namely students of IAI At-Taqwa Bondowoso and STIS Abu Zairi Bondowoso with a population of 220 people, and the sample in this study was 135 respondents. The sampling method used the Isac Micheal formula with a margin of error of 5 percent (Sig.0.05), and used the Simple Random Sampling method. The data collection technique used a questionnaire survey. The analysis hypothesis using multiple linear regression analysis. Based on the results of the research that has been carried out, it shows that the results of the multiple linear regression test are, (1) the religiosity variable has a significant effect on the interest in buying halal food products online for students of the Islamic economics study program at Islamic religious colleges (PTKI) in Bondowoso Regency, where the significance value is 0.000 0.05 (a = 5%), so the hypothesis is accepted. (2) the Islamic business ethics variable has a significant effect on the interest in buying halal food products online for students of the Islamic economics study program at Islamic religious colleges (PTKI) in Bondowoso Regency, where the significance value is 0.000 < 0.05 (a = 5%), so the hypothesis is accepted.